Repotenciación de un banco de pruebas para aislamiento de motores eléctricos. - Narvaez Pardo, Jonathan Leonardo (2010)
This research work aims at repowering a Test Bench for Electric Motor Insulation. Because the control winding insulation of electric motors is a matter of extreme importance in the maintenance of these machines, we propose that this work is the application for the winding check that these are not necessarily damaged. Instruments was implemented the latest technology which will serve satisfactorily for the electrical measurements lecturación and correct learning of students in the area. Another aspect that boost the performance of the benchmark above is to serve as a didactic element, as well as the conditions, it is possible to visualize the effect called electric arc, although the intensity that exists in the secondary winding is reduced by the medium voltage, as I indicated, ranging from 1000-2000 volts. This work is also composed of different practices which are designed for the proper use and learning of students who are training in Area